Factors Causing Work Stress Levels In Oil Palm Harvesting Workers At PT. Cipta Davia Mandiri In Kutai Timur District - Felicia Conifianti; Rosdiana; Heri Purwanto (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2022)
Background: plantation activities in the form of harvesting and caring for oil palm require energy or labor or a heavy workload because at the time of these activities' workers need a lot of stamina or energy, especially the production department or harvester section. In connection with these stages, careful handling is needed to prevent work accident disorders including psychosocial disorders in the form of work stress. To anticipate the occurrence of work stress, workers need to be given an understanding of occupational safety and health (K3) through knowledge of factors that cause work stress. Research Methods: quantitative with the type of research that is analytic survey using cross sectional approach. The population in this study were workers harvesting oil palm PT. Cipta Davia Mandiri in East Kutai Regency, totaling 176 people. The sample is 122 respondents. Data analysis using the Chi-Square test. Results: there was an effect of age on the level of work stress in oil palm harvesting workers (p value: 0.000 <: 0.05). There is an effect of working period on the level of work stress on oil palm harvesting workers (p value: 0.000 <: 0.05). There is an effect of workload on the level of work stress on oil palm harvesting workers (p value: 0.013 <: 0.05). Conclusion: age, period of work and workload are factors that cause work stress levels. It is recommended that harvesters avoid work stress, need to create a decent work environment by fostering a family atmosphere and attitude and find solutions to solve problems.